Terrestrial and Celestial Frontiers in Late Antiquity - Ivić, Nenad (Array, 2000)
This paper discusses the theoretical and practical implications of the Roman conception of frontier in Late Antiquity. Ancient sources (Aelius Aristides, Anonimus de rebus bellicis, historians) are contrasted to modern research (Isaac, Whittaker). It is focused on the parallelism between the transformation of the map of the celestial world brought out by Christianity and the emergence of the so-called Middle Groungor frontier-zone in the West, which, during the disintegration of the Empire in the fifth century, constituted the center of the newly formed successor states.